Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament Terhadap Hasil Belajar Matematika - Sri Damayanti; M Tohimin Apriyanto (JKPM (Jurnal Kajian Pendidikan Matematika), 2017)
The research is aimed to determine the Impacts of Cooperative Learning  type TGT ( Teams Games Tournament) on Mathematics Achievement at SDI Alfalah 1 Petang. Technique analysis used t test after fulfill a series of normality and homogeneity test. Based on normality test the data is in normal distribution, and for homogeneity through fisher test the data is homogen. Based on the research , it can be concluded that the average of student’s  achievement through cooperative TGT  learning is more than cooperative learning type NHT (Numbered Heads Together). So, Cooperative Learning type TGT has positive Impacts on student’s mathematics achievement on the students grade V at SDI Alfalah 1 Petang.